MENUMBUHKAN SIKAP SAINS CALON GURU ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS KONTEKSTUAL - Burhan, Burhan (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2014)
Attitude grown early science student teachers to early childhood, does notmean they have to be a60n expert science education or science teachersare experts. This attitude is not developed for the purpose of short-term,but the long-term. Learning is expected to take effect in early childhoodwould be a knowledge base, which leads them into a golden generation inthe future. The generation that has sensitivity to the surroundingenvironment, sensitive to the environment that gave birth to generationsof defenders surrounding environment. Learning science contextuallyfacilitate student understanding of science. Students are able to explainverbally about the material they are learning. Science materials that areabundant and free in their natural laboratories facilitate peace with thefamous natural complex. They were able to assemble independently ofscience in oral form, though still very limited, if knowledge gained ispresented in written form. Difficulty wrote early science knowledgepossessed lies in their inability to describe what has been done by usingthe active voice.Keywords : Early science, science attitude, contextual-based learning.